Epidemiology of the symptoms of menopause – an intercontinental review - Makara-Studzińśka, Marta Teresa; Kryś-Noszczyk, Karolina Maria; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction : The age of menopause is a time of many changes in the psychophysical-social functioning of women, with reduced ovarian hormonal activity and estrogen levels. The most common, troublesome symptoms of menopause age include depressive disorders, sleep disorders, sexual dysfunction, discomfort associated with muscle pain, joint aches, osteoporosis and characteristic hot flashes. Aim of the study is to determine and compare the rate of menopausal symptoms among women living in continents of both Americas, Africa, Australia and Eurasia. Material and methods : The results of this work were obtained in 2014 on the basis of the data from a review of the 64 most important studies using the PubMed database. Research published in the period 2000-2014, from Africa, both Americas, Australia and Eurasia, were taken into account. Results : The prevalence of menopausal symptoms in African women is disconcertingly high. Women from South America complain about occurrence of depressive, sexual dysfunctions and discomfort associated with muscle pain and joint aches. Symptoms most reported by women in the United States are pains associated with muscles and joints. Women in Australia suffer mainly due to vasomotor symptoms and sexual dysfunction, while in the group of women surveyed in Asia there is observed an alarming increase in the proportion of women reporting depressive disorders. In Europe there was a much greater incidence of sleep disorders and depressive disorders. Conclusions : Women around the world suffer from ailments characteristic for the menopausal period regardless of ethnic origin, skin color or socio-demographic factors.